Immigration for the purpose of training – what does the route into German vocational education and training from third countries look like? - Studthoff, Alexander [Verfasser] (My University, 2022)
"The Skilled Immigration Act (FEG) has been in force since March 2020 and extends opportunities for immigration by international skilled workers. The possibilities of coming to Germany to pursue vocational education and training have also been expanded. This article now considers how legal provisions are being implemented: Which challenges do trainees and trainers encounter, and how can things be optimised further?" (BIBB-Doku)
Keywords: P 1.5 Migranten; 370; Ausländer; Drittstaat; Einwanderung; Berufsausbildung; Rechtliche Regelungen